Implementation of Profile Matching Methods In A Mobile Based Adolescent Nutritional Assesment Systems - Bambang Agus Herlambang; Febrian Murti Dewanto; Aris Trijaka Harjanta; Vilda Ana Veria Setyawati (Jurnal Transformatika, 2018)
The use of mobile apps in knowing the problems as early as possible was considered effective. The application of mobile applications required today was an application that could help determine various health problems. The health problems discussed in this study were the nutritional status of adolescents. The method of measuring the nutritional status used was the BMI / A method. Profile Matching method in built mobile application is used to rank the nutritional status of adolescents. Aspect of nutritional status assessment in this research was physical aspect (BMI/A and Physical Activity) with 70% and Non-Physical Aspect (Eating & Socioeconomic Aspect) with 30% assessment percentage. Core factor in the determination of nutritional status were the Category of BMI and Frequency of Eating. While, secondary factor were food pattern and socio Economics. The results of mobile application implementation with Profile Matching method in this research there were several forms for the process of ranking the status of Adolescent Nutrition. The form contained in Administrator features include Administrator Login Form, Aspect Setup Form, Sub Aspect Setting Form, Physical Activity Setting Form, Form Setting Frequency Diet, Setting Form BMI/A, Economic Condition Set Form, Setting Form Weight Gap Value. In the User Features there was an Assessment form and a page to see the results of ranking the nutritional status of adolescents.